The Effect of E-Service Quality and Brand Image on E-Satisfaction with Customer Loyalty as an Intevening Variable - Yuwono, Daniel; Anggiani, Sarfilianty (JURNAL BISNIS STRATEGI, 2024)
The research to analyze and test the influence of brand image and e-service quality on e-loyalty with e-satisfaction as an intervening variable for Shopee consumers in Semarang City. The population of this research is Shopee consumers in Semarang City. Data was obtained using an online questionnaire via Google Form, namely 65 respondents. The data analysis method used is descriptive analysis and Partial Least Square analysis (SEM-PLS). Analysis is assisted by the Smart PLS 3.0 program. The research results show that e-service quality (X1) has a positive and significant effect on customer satisfaction (Y1), brand image (X2) has a negative and insignificant effect on customer satisfaction (Y1), e-service quality (X1) has a positive and significant effect on customer loyalty (Y), brand image (X2) has a positive and significant effect on customer loyalty (Y), customer satisfaction (Z) has a positive and significant effect on customer loyalty (Y), customer satisfaction (Z) improves e-service quality relationships (X1) to customer loyalty (Y), customer satisfaction (Z) increases the relationship between brand image (X1) to customer loyalty (Y).